Geographic information system in determining flood and safe zone for flood mitigation - Nur, Nur Khaerat; Chaerul, Muhammad; Azis, Abdul (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2021)
Computer-based technology has pervaded practically every aspect of human life in the modern era. Through diverse information systems, various fields have employed computer-based technology to build theories and their applications. Geographic Information System (GIS) technology is one type of computer-based system that is widely employed. Various disciplines can use Geographic Information System (GIS) technology to research and map flood zones. The research approach employed is the employment of ARC GIS 10.5 system technology to determine the flood zone's features. Pampang, Tamamaung, Sinri Jala, and Karuwisi Utara are four villages that are flood-prone locations that are included in the warning zone, according to the results of data processing using GIS software and data analysis illustrated from mapping the flood area in Panakkukang District. There are 1,985 hectares in the Rappocini sub-district, which is included in a vulnerable region, namely Bantabantaeng Village, and 145,709 hectares in Karunrung Village, Gunung Sari, Bontomakkio, Tidung, Kassi-Kassi, Mappala. Parts of the Manggala, Bangkala, and Borong regions, as well as sub-districts of Manggala, are included in the vulnerable areas. Tamalanrea Indah, Tamalanrea Jaya, and Tamalanrea sub-districts are the Tamalanrea sub-districts that have been designated as vulnerable zones.